'Closing the loop' in biological systems modeling-from the in silico to the in vitro - Kiparissides, Alexandros; Koutinas, Michalis; Kontoravdi, Cleo; Mantalaris, Athanasios A.; Pistikopoulos, Efstratios N. (My University, 2011)
This work presents a holistic 'closed loop' approach for the development of models of biological systems. The ever-increasing availability of experimental information necessitates the advancement of a systematic methodology to organise and utilise these data. Herein, we present a biological model building framework that maps the treatment of the information from the initial conception of the model, through its experimental validation and finally to its application in model-based optimisation studies. We highlight and discuss current issues associated with the development of mathematical models of biological systems and share our perspective towards a holistic 'closed loop' approach that will facilitate the control of the in vitro through the in silico.
Keywords: Model analysis; Biological systems model development; Sensitivity analysis; Design of experiments